2020
DOI: 10.20546/ijcmas.2020.902.075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Nitrogen Levels and Varieties on Protein and Nitrogen Content in Grain and Nitrogen Uptake by Barley (Hordeum vulgare L.) in Sodic Soil

Abstract: Rabi season of 2016-17 to study the performance of barley varieties under various nitrogen levels in sodic soil. The trial was laid out in Split Plot Design. Nitrogen levels (60, 75 and 90 kg N ha -1 ) were kept in main-plots and varieties (RD-2907, RD-2552, NDB-1173 and RD-2794 in sub-plots with three replications on sodic soils having low organic carbon (0.38 g kg -1 ), available nitrogen (185.0 kg ha -1 ), phosphorus (15.25 kg ha -1 ) and potassium (265 kg ha -1 ). Data manifested to nitrogen content and up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Due to higher green forage yield (Table 1), seed yield (Table 1) and straw yield (Table 1) after the treatment of 120 kg nitrogen per hectare, the dual purpose barley seed equivalent yield increased. Findings from Yadav et al (2003) and Singh et al (2009) also noted similar results.…”
Section: Seed Equivalent Yield (Kg/ha)supporting
confidence: 67%
“…Due to higher green forage yield (Table 1), seed yield (Table 1) and straw yield (Table 1) after the treatment of 120 kg nitrogen per hectare, the dual purpose barley seed equivalent yield increased. Findings from Yadav et al (2003) and Singh et al (2009) also noted similar results.…”
Section: Seed Equivalent Yield (Kg/ha)supporting
confidence: 67%
“…Along with intensive selection work, scientific research on the introduction of new species into culture, including local flora, especially in regions rich in natural species diversity, remains relevant at the present time [33,34].…”
Section: Resultsmentioning
confidence: 99%
“…The lowered protein content of jute may have resulted from reduced nitrogen uptake from the soil. Earlier studies showed that the protein content of plants increases with increasing soil nitrogen [33,34]. The reduced nitrogen uptake may be due to the competition caused by 6 Mexican sunflower plants per pot.…”
Section: Discussionmentioning
confidence: 98%
“…(2) Variance associated with the effects of the Year by treatment (fixed effects) interaction expressed as a percentage of the sum of the total variance associated with the effect of Year. (3) DF-degree of freedom.…”
Section: Climatic Datamentioning
confidence: 99%
“…in the Fertile Crescent [2]. It is an important crop, especially in areas where wheat cultivation is not feasible, thanks to some of its characteristics such as greater environmental adaptability, lower water requirements, tolerance to stress conditions, and ability to grow in either saline [3] and alkaline soils [4]. Barley has several applications, e.g., as seed in the malting industry and as livestock feed as a whole plant for hay, silage, green feed, or even as straw [5].…”
Section: Introductionmentioning
confidence: 99%